Iron oxide‐loaded polymer scaffolds for non‐invasive hyperthermic treatment of infiltrated cells. Issue 12 (4th September 2020) - Lam, Tiffany; Moy, Alyssa; Lee, Hak Rae; Shao, Qi; Bischof, John C.; Azarin, Samira M.
Abstract: Focal therapies such as hyperthermia have been successfully used to treat solid localized tumors; however, they are not easily applied to cancers that may present in a disseminated form such as ovarian cancer. To address this need, iron oxide (IO) particles were incorporated into microporous poly(caprolactone) scaffolds previously shown to recruit disseminating cancer cells. Under an alternating magnetic field, IO‐loaded scaffolds exhibited heating and killed ID8 ovarian cancer cells in vitro. After implantation in the intraperitoneal cavity of mice, IO‐loaded scaffolds became infiltrated with tissue after 6–7 weeks, and infiltrated cells were successfully treated ex vivo. Finally, IO‐loaded scaffolds noninvasively killed infiltrated cells in vivo as evidenced by decreases in number of nuclei. These studies demonstrate the promising use of IO‐loaded scaffolds as a tool for noninvasive hyperthermia, which could be an innovative modality for treatment of disseminated cancers.